Treatment as prevention for hepatitis C virus in the Middle East and North Africa: a modeling study - Ayoub, Houssein H.; Mahmud, Sarwat; Chemaitelly, Hiam; Abu-Raddad, Laith J. (Frontiers in Public Health, 2023)
Background: Direct-acting antivirals opened an opportunity for eliminating hepatitis C virus (HCV) infection in the Middle East and North Africa (MENA), the region most affected by HCV infection. Impact of HCV treatment as prevention (HCV-TasP) was investigated in 19 MENA countries. Methods: An age-structured mathematical model was used to assess program impact using epidemiologic and programming measures. The model was fitted to a database of systematically gathered HCV antibody prevalence data. Two main scenarios were investigated for the treatment roll-out to achieve i) 80% reduction in HCV incidence by 2030, and ii) incidence rate <1 per 100,000 person-years by 2030. Results: In the target-80%-incidence-reduction scenario, number of treatments administrated by 2030 ranged from 2,610 in Lebanon to 180,416 in Sudan, and treatment coverage ranged between 40.2% and 78.4%. By 2030, prevalence of chronic infection ranged between 0.0% and 0.3%, and incidence rate, per 100,000 person-years, ranged between 0.9 and 16.3. Program attributed reduction in incidence rate ranged between 47.8% and 81.9%, and number of averted infections ranged between 401 and 68,499. Number of treatments needed to prevent one new infection ranged from 1.7 in Oman to 25.9 in Tunisia. In the target incidence rate <1 per 100,000 person-years scenario, number of treatments administrated by 2030 ranged from 3,470 in Lebanon to 211,912 in Sudan, and treatment coverage ranged between 55.5% and 95.9%. By 2030, prevalence of chronic infection was less than 0.1%, and incidence rate, per 100,000 person-years, reached less than 1. Program attributed reduction in incidence rate ranged between 61.0% and 97.5%, and number of averted infections ranged between 559 and 104,315. Number of treatments needed to prevent one new infection ranged from 1.3 in Oman to 25.9 in Tunisia. Conclusion: HCV-TasP is an effective and indispensable prevention intervention to control MENA’s HCV epidemic and to achieve elimination by 2030.